Tobacco smoking during breastfeeding increases the risk of developing metabolic syndrome in adulthood: Lessons from experimental models. (October 2020) - Miranda, Rosiane A.; Gaspar de Moura, Egberto; Lisboa, Patrícia Cristina
Abstract: Metabolic syndrome (MetS) is characterized by increased abdominal fat, dyslipidemia, diabetes mellitus and hypertension. A high MetS prevalence is strongly associated with obesity. Obesity is a public health problem in which several complex factors have been implicated, including environmental pollutants. For instance, maternal smoking seems to play a role in obesogenesis in childhood. Given the association between endocrine disruptors, obesity and metabolic programming, over the past 10 years, our research group has contributed to studies based on the hypothesis that early exposure to nicotine/tobacco causes offspring to become MetS-prone. The mechanism by which tobacco smoking during breastfeeding induces metabolic dysfunctions is not completely understood; however, increased metabolic programming has been shown in studies that focus on this topic. Here, we reviewed the literature mainly based in light of our latest data from experimental models. Nicotine or tobacco exposure during breastfeeding induces several endocrine dysfunctions in a sex- and tissue-specific manner. This review provides an updated summary regarding the hypothesis that early exposure to nicotine/tobacco causes offspring to become MetS-prone. An understanding of this issue can provide support to prevent long-term disorders, mainly related to the risk of obesity and its comorbidities, in future generations. Graphical abstract: Image 1 Highlights: Metabolic syndrome and obesity are linked with endocrine disruptors exposure. Tobacco during critical phases of life leads to metabolic dysfunctions later in life. Nicotine and tobacco exposure during lactation cause different effects in offspring. Experimental models in this area could be the key for further clinic investigations.